(untitled) (Bangladesh Journal of Pharmacology, 2016)
The study was aimed to evaluate the knowledge, perception and prepared-ness of the 4th year students of three medical colleges of Bangladesh during January 2016. The questionnaire was designed to evaluate knowledge, perception and preparedness about antimicrobial stewardship and resistance. Out of two hundred and seventy six students provided with questionnaire, one seventy one (82%) had responded completely. The term antimicrobial stewardship was familiar to only 6% students. Thirty nine percent respon-dents correctly responded on antibacterial spectrum. Seventy two percent students mentioned that teaching on antimicrobial should begin from 3rd year and 89% felt necessity of spending more time on antimicrobials. This study revealed that future prescribers recognize the necessity of targeted teaching on antimicrobial to prepare them to prescribe antimicrobials rationally.